2018
DOI: 10.1523/eneuro.0245-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

The Mixed-Lineage Kinase Inhibitor URMC-099 Protects Hippocampal Synapses in Experimental Autoimmune Encephalomyelitis

Abstract: Treatments to stop gray matter degeneration are needed to prevent progressive disability in multiple sclerosis (MS). We tested whether inhibiting mixed-lineage kinases (MLKs), which can drive inflammatory microglial activation and neuronal degeneration, could protect hippocampal synapses in C57BL/6 mice with experimental autoimmune encephalomyelitis (EAE), a disease model that recapitulates the excitatory synaptic injury that occurs widely within the gray matter in MS. URMC-099, a broad spectrum MLK inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 60 publications
2
9
0
Order By: Relevance
“…The present study demonstrates URMC-099’s therapeutic efficacy in a mouse model of orthopedic surgery-induced PND and adds to the growing literature documenting URMC-099’s neuroprotective effects [14, 15, 17, 18]. URMC-099 was discovered initially in search of potent MLK3 inhibitors with favorable CNS penetration properties.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The present study demonstrates URMC-099’s therapeutic efficacy in a mouse model of orthopedic surgery-induced PND and adds to the growing literature documenting URMC-099’s neuroprotective effects [14, 15, 17, 18]. URMC-099 was discovered initially in search of potent MLK3 inhibitors with favorable CNS penetration properties.…”
Section: Discussionsupporting
confidence: 58%
“…Using a variety of preclinical models of disease that feature neuroinflammation, including HIV-1-associated neurocognitive disorders (HAND) [14], Alzheimer’s disease (AD) [15, 16], and multiple sclerosis (MS) [17], we have demonstrated the therapeutic efficacy of the small-molecule, blood-brain barrier (BBB)-permeable, mixed-lineage kinase 3 (MLK3) inhibitor URMC-099 [15, 16]. In addition to exhibiting favorable pharmacokinetic and toxicity profiles in rodents, URMC-099 possesses “broad-spectrum” activity due to its ability to inhibit multiple kinases, and consequently downstream signaling pathways, that mediate pathological interactions between innate immune cells and end-organ target cells (such as neurons) [14, 1719]. Although URMC-099 and other immunomodulatory approaches can reduce untoward microglial responses in a variety of chronic neuroinflammatory settings, they can pose translational concerns in the context of acute perioperative recovery, such as impairing normal healing and tissue regeneration after surgical trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Besides reduction in dendritic spine number, the postsynaptic scaffold protein Homer1 is also affected in the stratum radiatum after depletion of TBC1D24 in vivo. Although co-staining with a presynaptic marker has not been performed, given that majority of Homer1 or PSD-95 puncta are co-localized with each other and apposed to presynaptic terminals in the hippocampus in vivo [67,68,69], the number of postsynaptic puncta after single Homer1 or PSD-95 staining has been used to reflect the density of excitatory synapses [70,71,72,73]. Knockdown of TBC1D24 by shRNA reduces the density of Homer1 puncta in CA1 neurons, while both TBC1D24 knockdown and TBC1D24 F251L/+ heterozygous mutation lead to reduction of Homer1 puncta size and intensity in the hippocampus in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Our lab has previously shown that EAE immunization results in significant synapse loss in the CA1-statum radiatum of the hippocampus, which is largely spared from demyelination [40,53]. To determine if the EAE hippocampus also exhibits increased complement production and deposition in EAE that could make synapses vulnerable to phagocytosis by glia, we first analyzed C1q and C3 protein and mRNA expression by Western blot and qPCR.…”
Section: C1q and C3 Expression In Eae Hippocampusmentioning
confidence: 99%